PENGARUH MOTIVASI KERJA GURU TERHADAP KINERJA GURU SMP NEGERI 6 PEKANBARU - Mely Jumika Mely Jumika; Suarman '; Sumarno ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this study was to determine the effect of work motivationof teacher on teacher performance on SMP Negeri 6 Pekanbaru. The population in thisstudy all teacher in the SMP Negeri 6 Pekanbaru, with a sample of 30 people. The dataused in this study is primary data. Primary data were obtained from the respondentsanswer. Analysis of the data used is simple linear regression analysis with significancelevel of 5%. Data processing is done with the help of SPSS software version 17.0 From theresults of research on regression analysis result obtained Y = 38.019 + 0.182X whichmeans teacher performance is influenced by the work motivation of teacher. While the testis based on the t value obtained t count > t table (11.383 > 1.697) or the Sig. 0.000 < 0.05,means that the hypothesis is accepted means that work motivation of teacher has significantinfluence on teacher performance. Coefficient of determination obtained is 82,22 %. While17,8% is influenced by other variables not known.Key words : Work Motivation of Teacher , Teacher Performance